PENGARUH GREEN MARKETING, KESADARAN LINGKUNGAN DAN KESEHATAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PANGAN ORGANIK MELALUI SIKAP - Caselia Ajeng Puspitasari; Lilik Noor Yuliati; Farit Afendi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
This study did to analyze the effect of green marketing, environtmental awareness and health on purchasing decisions of organic food products through attitudes. The purpose of this study were (1) To analyze effect of green marketing, environmental awareness, and health awareness on attitudes. (2) To analyze effect of green marketing, environmental awareness, health awareness, and attitudes on purchasing decisions of organic food products. (3) To formulate managerial implications for enhanced the purchase of organic products. The data in this study was analyzed by using Structural Equation Modeling (SEM) with total of sample was 220 respondents. The results of this study were showed that green marketing and environmental awareness had an effect on attitudes. Green marketing and health awareness had an effect on purchasing decisions of organic food products. Managerial implications that could be given were to proved that the product was safe to consumed by ensured this product had been certified, company always improved their promotion with using social media or by any event, and company guaranteed the product they produced was eco-friendly. Keywords: attitudes, environmental awareness, green marketing, health awareness, purchasing decisions